Folk Theatre Elements: A Theoretical Framework of Performance - Rai, Parshuram (Prajnik Bimarsha प्राज्ञिक विमर्श, 2025)
This article examines the essential elements of folk theatre that shape its folk dramaturgical form. These elements are explored not only as artistic techniques but also as carriers of oral tradition, collective memory, and cultural identity. The study argues that folk theatre’s improvisational style, integration of ritual symbolism, and emphasis on communal interaction produce a holistic mode of performance that contrasts with Eurocentric theatrical models. Methodologically, employs interdisciplinary methods including participant, observation, direct engagement, and both emotional and physical involvement and AI tool to capture the lived realities of folk theatre elements within its socio-cultural context. This integrated approach ensures a robust investigation of folk theatre elements while contributing to wider debates on tradition, cultural sustainability, and technological mediation in performance studies.